2016
DOI: 10.1002/anie.201605865
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of meta‐Terphenyl‐2,2′′‐diols by Anodic C−C Cross‐Coupling Reactions

Abstract: The anodic C-C cross-coupling reaction is a versatile synthetic approach to symmetric and non-symmetric biphenols and arylated phenols. We herein present a metal-free electrosynthetic method that provides access to symmetric and non-symmetric meta-terphenyl-2,2''-diols in good yields and high selectivity. Symmetric derivatives can be obtained by direct electrolysis in an undivided cell. The synthesis of non-symmetric meta-terphenyl-2,2''-diols required two electrochemical steps. The reactions are easy to condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(50 citation statements)
references
References 72 publications
0
45
0
5
Order By: Relevance
“…Die Reaktion eines Amids mit 5b im Rundkolben bençtigte 48 Stunden, um das Carbazolderivat 17 in 60 %A usbeute zu erhalten. [19] Zusammenfassend wurde ein effizienter und zuverlässiger elektrochemischer Generator hypervalenter Iodreagenzien entwickelt, der gefährliche chemische Oxidationsmittel durch Elektrizitäte rsetzt. Die Erhçhung der Verweilzeit auf 60 min bei 50 8 8Cf ührte zur Isolierung des Carbazols in 48 %A usbeute (Eintrag 13).…”
unclassified
“…Die Reaktion eines Amids mit 5b im Rundkolben bençtigte 48 Stunden, um das Carbazolderivat 17 in 60 %A usbeute zu erhalten. [19] Zusammenfassend wurde ein effizienter und zuverlässiger elektrochemischer Generator hypervalenter Iodreagenzien entwickelt, der gefährliche chemische Oxidationsmittel durch Elektrizitäte rsetzt. Die Erhçhung der Verweilzeit auf 60 min bei 50 8 8Cf ührte zur Isolierung des Carbazols in 48 %A usbeute (Eintrag 13).…”
unclassified
“…using chemical oxidizers demonstrated that this electrochemical cross-coupling can easily compete with conventional methods. [109] Recent studies have highlighted its robustness, [111] and extended the applicability of this process to the electrochemical synthesis of partially protected non-symmetric biphenols, [112] protected bianiline derivatives [113] (Scheme 34, top), and m-terphenyl-2,2''-diols by twofold CÀCc ross-coupling [114] (Scheme 34, bottom). Thec rosscoupling of phenols with heterocycles was recently described.…”
Section: Anodic Couplings By Càha Ctivationmentioning
confidence: 99%
“…Various electrochemical cross-couplings enabled by CÀH activation developed by Waldvogel and co-workers. [107][108][109][110][111][112][113][114] Scheme 35. General cyclization of olefins with trapping nucleophiles.…”
Section: Electrochemical Synthesis Of Heterocyclesmentioning
confidence: 99%
“…[2][3][4] Schema 2. [16] Die anodische Umsetzung verschiedenster Arylsysteme führte zur erfolgreichen Synthese von symmetrischen und nicht-symmetrischen Biphenolen, [17][18][19] Arylphenolen, [20,21] meta-Terphenyl-2,2''-diolen, [22] 2,2'-Diaminobiphenylen, [23] Hydroxphenylthiophenen, [24] Hydroxyphenylbenzofuranen [25] und Hydroxyphenylnaphthylaminen [26] durch Durchführung einer dehydrierenden C,C-Kreuzkupplung.M it besonderem Augenmerk auf die anodischen Kreuzkupplungsreaktionen von Phenolen mit Heterocyclen war die Kupplung von Thiophenen jedoch nur in geringen Ausbeuten mçglich. [8][9][10] [*] S. Lips [12] oder Nheterocyclischen Carbenen [13] (NHCs) entwickelt, die zumindest eine einfache C,H-Aktivierung ermçglichen.…”
unclassified